Lung Adenocarcinoma Global Profiling Identifies Type II Transforming Growth Factor-β Receptor as a Repressor of Invasiveness - Borczuk, Alain C. (American Thoracic Society, 2005)
Rationale: Lung adenocarcinoma histology and clinical outcome are heterogeneous and associated with tumor invasiveness. Objectives: We hypothesized that invasiveness is associated with a distinct molecular signature and that genes differentially expressed in tumor or adjacent stroma will identify cell surface signal transduction and matrix remodeling pathways associated with the acquisition of invasiveness in lung adenocarcinoma. Main Results: Microarray analysis of microdissected noninvasive bronchioloalveolar carcinoma (BAC) and invasive adenocarcinoma and adenocarcinoma-mixed type with BAC features identified transcriptional profiles of lung adenocarcinoma invasiveness. Among the signature set that was lower in adenocarcinoma-mixed compared with BAC was the type II transforming growth factor β (TGF-β) receptor, suggesting downregulation of TGFβRII is an early event in lung adenocarcinoma metastasis. Immunostaining in independently acquired specimens demonstrated a correlation between TβRII expression and length of tumor invasion. Repression of TGFβRII in lung cancer cells increased tumor cell invasiveness and activated p38 mitogen-activated protein kinases. Microarray analysis of invasive cells identified potential downstream mediators of TGFβRII with differential expression in lung adenocarcinomas. Conclusions: The repression of type II TGF-β receptor may act as a significant determinant of lung adenocarcinoma invasiveness, an early step in tumor progression toward metastasis.